2015
DOI: 10.5897/ajmr2015.7557
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of xylanase production by indigenous thermoalkalophillic Bacillus sp.

Abstract: Xylanases are an important class of hydrolytic enzymes with a wide range of industrially important applications especially in paper and pulp industry. The present study aimed to take the advantage of statistical approach of optimization to investigate the interactive effects of prominent process factors involved in xylanase production. A novel bacterial isolate Bacillus sp. MCC 2727 was isolated from soil possessing xylanase producing ability at alkaline pH (9.2) and optimum temperature of 50°C. Using the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In enzyme production, metals demonstrate varied actions in their ability to act as effectors [33]. The presence of specific metal ion along with essential nutrient sources can inhibit or enhance amylase activity [34]. Therefore, the supplementation of the test metal ions into the production medium showed that Hg 2+ , Cu 2+ and Pb 2+ inhibited amylase production (when compared to the activity of the control (fermentation without metal supplement) which is taken as 100% (Figure 4).…”
Section: Metal Ion On Amylase Yieldmentioning
confidence: 99%
“…In enzyme production, metals demonstrate varied actions in their ability to act as effectors [33]. The presence of specific metal ion along with essential nutrient sources can inhibit or enhance amylase activity [34]. Therefore, the supplementation of the test metal ions into the production medium showed that Hg 2+ , Cu 2+ and Pb 2+ inhibited amylase production (when compared to the activity of the control (fermentation without metal supplement) which is taken as 100% (Figure 4).…”
Section: Metal Ion On Amylase Yieldmentioning
confidence: 99%
“…The R 2 value indicated goodness of fit of model, but high R 2 may be due to other non-significant variables and adj. R-squared value must be considered to manage the R 2 [26]. Similarly, in other studies RSM was carried out for optimization and the adj.…”
Section: Central Composite Design (Ccd)mentioning
confidence: 99%